2021
DOI: 10.3389/fendo.2021.670719
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Classes of Small Non-Coding RNAs With Potential Implications in Diabetes and Associated Metabolic Disorders

Abstract: Most of the sequences in the human genome do not code for proteins but generate thousands of non-coding RNAs (ncRNAs) with regulatory functions. High-throughput sequencing technologies and bioinformatic tools significantly expanded our knowledge about ncRNAs, highlighting their key role in gene regulatory networks, through their capacity to interact with coding and non-coding RNAs, DNAs and proteins. NcRNAs comprise diverse RNA species, including amongst others PIWI-interacting RNAs (piRNAs), involved in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 160 publications
(210 reference statements)
0
11
0
Order By: Relevance
“…The potential of piRNAs to affect numerous downstream pathways can bring a significant impact on the molecular and functional landscape of cancer cells, promoting attempts to create future therapies that specifically target piRNAs (Jacovetti et al, 2021). Numerous preclinical research employing piRNA-based therapeutic compounds has already demonstrated outstanding results in terms of the capacity of piRNAs to influence the malignant features of HCC, CRC and GC cells (Cheng et al, 2012;Law et al, 2013;Mai et al, 2018) (Figure 2).…”
Section: Therapeutic Approaches Using Piwi-interacting Rnasmentioning
confidence: 99%
“…The potential of piRNAs to affect numerous downstream pathways can bring a significant impact on the molecular and functional landscape of cancer cells, promoting attempts to create future therapies that specifically target piRNAs (Jacovetti et al, 2021). Numerous preclinical research employing piRNA-based therapeutic compounds has already demonstrated outstanding results in terms of the capacity of piRNAs to influence the malignant features of HCC, CRC and GC cells (Cheng et al, 2012;Law et al, 2013;Mai et al, 2018) (Figure 2).…”
Section: Therapeutic Approaches Using Piwi-interacting Rnasmentioning
confidence: 99%
“…In contrast, the conversion of RNA load from piRNAs to tsRNAs during sperm maturation also suggests that tsRNAs are involved in epigenetic regulation [ 56 ]. A related study showed that mice deficient in DNA methyltransferase-2 (DNMT2) prevented high-fat diet-induced intergenerational genetic disorders [ 57 ], while the absence of DNMT2 abolished alterations in sperm tsRNAs modification and expression, suggesting a key role for tsRNAs in epigenetic mechanisms [ 58 ]. The above studies indicate that tsRNAs are equivalent to new piRNAs in playing significant roles in the epigenetic regulation of organisms.…”
Section: Biological Functions Of Tsrnasmentioning
confidence: 99%
“…As tRFs can regulate biological processes through protein interactions (Jacovetti et al, 2021), we sought to unveil the molecular bases for the tiRNA-5 function by performing RNA pull-down assays in INS832/13 cells coupled to mass spectrometry. A biotinylated oligonucleotide of tiRNA-5 HisGTG was used as bait due to its enrichment in mitochondrial fractions and Mpc1 immunoprecipitation (Figures 7A and 7B).…”
Section: Interaction Of Tirna-5 Hisgtg With Rna-binding Proteinsmentioning
confidence: 99%